Avaliação do acoplamento do processo eletro-fenton com célula combustível microbiana para a degradação de glifosato em meio aquoso - Oliveira, Weverton Virgilino (2023)
The coupling of the electro-Fenton (EF) process with a microbial fuel cell (MFC), known as bioelectro-Fenton (BEF), is a bioelectrochemical system that has been applied as a promising technology for the degradation of emerging contaminants. In this dissertation, the performance of the BEF system in the degradation of glyphosate in aqueous media was evaluated. For this purpose, a double-chamber MCC was built, with the anode made of carbon felt, while the cathode was a gas diffusion electrode (GDE). A polypropylene-clay nanocomposite was used as the cation exchange membrane. For the biodegradation tests carried out in the anode chamber, the microorganism used was a bacterium of the species Serratia sp. isolated from a tropical peat bog located in the municipality of Santo Amaro das Brotas, state of Sergipe, Brazil (36º58'52.93"W, 10º49'3.63"S). The degradation rates of glyphosate in the application of the synthetic aqueous solution were determined at the anode of the MCC, obtaining values of 8.4%, 53.0% and 100.0% in 48 h of experiment for the abiotic control, open circuit (MCC CA) and closed circuit (MCC CF), respectively. At the cathode, the degradation rates in 48 h were 4.8%, 13.0% and 69.4% for CCM CA, the system without the addition of Fe2+ ions, and CCM CF, respectively. At the cathode, the degradation rates in 48 h were 4.8%, 13.0% and 69.4% for CCM CA, the system without the addition of Fe2+ ions, and CCM CF, respectively. The formation of a biofilm was identified on the carbon felt in the anode compartment and confirmed by infrared spectroscopy (FTIR) and scanning electron microscopy with energy dispersive spectroscopy (SEM-EDS). There was 100.0% biodegradation and degradation of glyphosate in both compartments of the BEF system, using fortified field samples (weir water), in 36 h of experiments. For AMPA, there was a 66.5% decrease in initial concentration after 24 h of experimentation in the anodic compartment and complete degradation and mineralization in the cathodic compartment. Therefore, the results showed the efficiency of the BEF system in eliminating the herbicide and that the bacterium Serratia sp. has sufficient electrogenic characteristics to generate current, which allows the use of this microorganism in coupled techniques.